Effect of Various Biochar Materials and Levels of Chicken Manure on Growth and Yield of Soybean - Suryani Sajar; Andi Setiawan; Adella Tri Anzani (International Forum of Researchers and Lecturers, 2024)
This study aims to determine the effect of various biochar materials and doses of chicken manure on soybean growth and yield. The research method used a 2 factorial Randomized Group Design. The first factor is the treatment of various biochar materials consisting of 4 levels, namely: no treatment, corn cob biochar, jengkol skin biochar, rice husk biochar. Factor II is chicken manure consisting of 0 ton/ha, 5 ton/ha, 10 ton/ha and 15 ton/ha. The results showed that the provision of biochar on the growth and yield of soybean plants had a significant effect on the parameters of stem diameter, number of pods, dry weight of seeds/plant, dry weight of 100 seeds. The provision of jengkol skin biochar gave the highest effect on stem diameter (1.750 cm), number of pods (181.60 pods), dry weight of seeds/plant (45.64 gr), weight of seed/m2 (442,98 g). The application of chicken manure on the growth and yield of soybean plants gives a significant effect on stem diameter, number of pods, dry weight of seeds/plant, dry weight of 100 seeds. The dose of chicken manure 15 tons/ha showed the highest effect on stem diameter, number of pods, dry weight of seeds/plant, dry weight of 100 seeds. The interaction of biochar and chicken manure fertilizer did not give a significant effect on all treatments.